Monetary policy transmission, bank market power, and wholesale funding reliance - Amina Enkhbold (Bank of Canada, 2023)
I study the impact of banking market concentration and wholesale funding reliance on the transmission of monetary policy shocks to mortgage rates. I empirically demonstrate that in the United States, banks with higher reliance on wholesale funding in concentrated (competitive) deposit markets transmit monetary policy shocks less (more) to mortgage rates. I study this imperfect transmission through the lens of a New Keynesian model with monopolistically competitive banks and costly access to wholesale funding. I find that high market power banks with greater wholesale funding transmit monetary policy less to deposit rates, generating lower liability. This leads to lower mortgage lending, house prices, and borrower consumption. If monetary policy shocks become persistent, this negative effect is amplified with banks shifting away from deposits more towards wholesale funding.
Keywords: E44; E52; G21; 330; Monetary policy transmission; Financial institutions; Inflation targets; Wholesale funding